Fusion of antigen to a dendritic cell targeting chemokine combined with adjuvant yields a malaria DNA vaccine with enhanced protective capabilities. - Kun Luo; Hong Zhang; Fidel Zavala; Arya Biragyn; Diego A Espinosa; Richard B Markham (PLoS ONE)
Although sterilizing immunity to malaria can be elicited by irradiated sporozoite vaccination, no clinically practical subunit vaccine has been shown to be capable of preventing the approximately 600,000 annual deaths attributed to this infection. DNA vaccines offer several potential advantages for a disease that primarily affects the developing world, but new approaches are needed to improve the immunogenicity of these vaccines. By using a novel, lipid-based adjuvant, Vaxfectin, to attract immune cells to the immunization site, in combination with an antigen-chemokine DNA construct designed to target antigen to immature dendritic cells, we elicited a humoral immune response that provided sterilizing immunity to malaria challenge in a mouse model system. The chemokine, MIP3αCCL20, did not significantly enhance the cellular infiltrate or levels of cytokine or chemokine expression at the immunization site but acted with Vaxfectin to reduce liver stage malaria infection by orders of magnitude compared to vaccine constructs lacking the chemokine component. The levels of protection achieved were equivalent to those observed with irradiated sporozoites, a candidate vaccine undergoing development for further large scale clinical trial. Only vaccination with the combined regimen of adjuvant and chemokine provided 80-100% protection against the development of bloodstream infection. Treating the immunization process as requiring the independent steps of 1) attracting antigen-presenting cells to the site of immunization and 2) specifically directing vaccine antigen to the immature dendritic cells that initiate the adaptive immune response may provide a rational strategy for the development of a clinically applicable malaria DNA vaccine.